How can artificial neural networks approximate the brain? - Shao, Feng; Shen, Zheng (Frontiers in Psychology, 2023)
The article reviews the history development of artificial neural networks (ANNs), then compares the differences between ANNs and brain networks in their constituent unit, network architecture, and dynamic principle. The authors offer five points of suggestion for ANNs development and eight points of challenge for the interdisciplinary field of brain simulation. Even though brain is a super-complex system with 10 11 neurons, its intelligence does depend rather on the neuronal types and their energy supply mode than the number of neurons. It might be possible for ANN development to follow a new direction that is a combination of multiple modules with different architecture principle and multiple computation, rather than very large scale of neural networks with much more uniformed units and hidden layers.